Motives behind national and regional approaches to health and foreign policy - Devi Lalita Sridhar; Kate Smolina (University of Oxford, Global Economic Governance Programme (GEG), 2012)
In recent years, health has risen as a strategic foreign policy and diplomatic concern across the world, becoming an important part of both formal and informal international relations. In this paper, we attempt to identify the motives behind national and regional approaches to health and foreign policy. We argue that even though the main drivers of the move towards linking health and foreign policy are traditional security concerns, some states also show signs of altruistic behaviour that extends beyond foreign policy interests. We suggest that this is likely due to strategic engagement by health advocates who have used the window of opportunity provided by recent infectious disease outbreaks to mainstream health into formal and informal strategies. As such, apparently altruistic acts towards global public health arise as positive externalities integrated into new policies that largely deal with other issues. We conclude that while national self-interest is likely to remain the main driving force behind foreign policy engagement in global public health, the strategic use of policy mechanisms by health advocates helps ensure that more altruistic behaviours are incorporated into government. These are small steps towards ensuring health and foreign policy engage in ways which are mutually beneficial.
Keywords: 330; global public health; foreign policy; international relations; policy mechanisms; security